2013
DOI: 10.1021/op400292m
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Development of Practical Routes to an Enantiomerically Pure C2-Symmetric Diamine Building Block

Abstract: Several routes to an enantiomerically pure C 2-symmetric diamine were evaluated and modified to scalable methods. A Zn/Me3SiCl-mediated reductive coupling of an imine was found to be superior to the other methods investigated, allowing us to safely prepare the enantiomerically pure diamine also on a large scale. One key step in this method was a highly efficient resolution of a stereoisomeric mixture of the diamine through salt formation with (−)-dibenzoyl-l-tartaric acid. The enantiomerically pure C 2-symmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…[18] The two C–C bonds in the ring are created in the same transformation, as opposed to traditional piperazine syntheses, based on multistep sequences of cyclization and reduction reactions (ketopiperazine,[20] pyrazine reduction[21] or intramolecular aza-pinacol coupling). [22] Using the best combination of these methods, a piperazine product like 3 a (see Table 1) would take no less than four steps in the making (even longer for more elaborated substituents or unsymmetrical analogs),[22a, 23] thus discouraging its exploration in catalysis.…”
mentioning
confidence: 99%
“…[18] The two C–C bonds in the ring are created in the same transformation, as opposed to traditional piperazine syntheses, based on multistep sequences of cyclization and reduction reactions (ketopiperazine,[20] pyrazine reduction[21] or intramolecular aza-pinacol coupling). [22] Using the best combination of these methods, a piperazine product like 3 a (see Table 1) would take no less than four steps in the making (even longer for more elaborated substituents or unsymmetrical analogs),[22a, 23] thus discouraging its exploration in catalysis.…”
mentioning
confidence: 99%
“…The diamine 45 was isolated with 73% yield as a mixture of rac/meso mixture in a 50/50 ratio. 25 Recently, this method has been selected for the synthesis on 100 g. 26 From 2,6-dimethylcyclohexanone 46 (83/17 cis/trans mixture) two diastereoisomers 47A and 47C were isolated respectively in 23% and 25% yield (Scheme 4). 23 More generally, the pinacol reaction of imine can take place in the presence of Zn/TMSCl.…”
mentioning
confidence: 99%
“…24 This method has been applied to the synthesis of ligand (R,R)and (S,S)-N,N 0 -dimethyl-1,2-diphenylethylene-1,2-diamine on 10 g scale. 25 Recently, this method has been selected for the synthesis on 100 g. 26 From 2,6-dimethylcyclohexanone 46 (83/17 cis/trans mixture) two diastereoisomers 47A and 47C were isolated respectively in 23% and 25% yield (Scheme 4). Three different products could have been obtained: two diastereoisomers (47A and 47B) and one pair of enantiomers (47C).…”
mentioning
confidence: 99%
“…In the first-generation synthesis, the activation was performed using HCl or aqueous ammonium chloride solutions. Our previous good experiences of using 1,2-dibromoethane/trimethylsilyl chloride (TMSCl) for the activation of zinc led us to try this combination in the present example also . Fortunately, we found that after quick activation of zinc using 1,2-dibromoethane and TMS-Cl sequentially followed by dropwise addition of the bromide, a controlled exotherm was obtained, and the amounts of zinc and bromide required were reduced to 3 and 1.1 equiv, respectively.…”
Section: Resultsmentioning
confidence: 93%